Related-party transactions, profitability, and tax avoidance: Evidence from Indonesia’s VAT reform - Tampubolon, Desy Miranda Christine; Setiabudi, Andang Wirawan (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
This study aims to analyze the effects of related party transactions and profitability on tax avoidance as a form of corporate tax management. High profitability may provide firms with greater opportunities to engage in tax management practices, whereas transactions with related parties may create loopholes for tax avoidance. External pressure increased following the change in the value-added tax (VAT) rate in 2022 from 10% to 11%, with a further increase to 12% planned. This policy may encourage firms to seek more advantageous tax-saving strategies. The research population consisted of industrial-sector companies listed on the Indonesia Stock Exchange during 2020–2023, with 233 firms selected using purposive sampling. Secondary data were obtained from the official IDX website. A quantitative approach employing Moderated Regression Analysis was used. The findings indicate that related party transactions and profitability positively influence tax avoidance, and that VAT rate increases moderate these relationships. The results provide implications for tax authorities to strengthen oversight during periods of VAT policy reform.